Pemetaan Kerentanan Banjir Dengan Pendekatan Geomorfologi Studi Kasus Di Kota Kendari = Flood Susceptibility Mapping of Kendari City Using Geomorphological Approach - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT The study was conducted at Kendari city, part of theWang-u catchment area. The aims of study are to identifi the flood prone area, the affected factors, and map the flood of the area. Three steps were conducted inthis research